Antiarthritic and Antihyperalgesic Properties of Ethanolic Extract from Gomphrena celosioides Mart. (Amaranthaceae) Aerial Parts - MacOrini, Luis Fernando Benitez; Radai, Joyce Alencar Santos; Maris, Rafael Souza; Silva-Filho, Saulo Euclides; Leitao, Maicon Matos; Andrade, Sérgio Faloni De; Gelves, Dayanna Isabel Araque; Salvador, Marcos Jose; Arena, Arielle Cristina [UNESP]; Kassuya, Cândida Aparecida Leite (Wiley, 2020)
Gomphrena celosioides Mart. (Amaranthaceae) is used in folk medicine as a natural analgesic, and in Brazil, the species of genus Gomphrena is used for rheumatism. However, scientific evidence which supports its popular use as an analgesic is scarce. This study assessed the antiarthritic and antihyperalgesic activities of the ethanolic extract obtained from G. celosioides aerial parts on Swiss or C57BL/6 mice. The antiarthritic and antihyperalgesic potential of Gomphrena celosioides was evaluated using paw edema, mechanical hyperalgesia, cold allodynia, carrageenan-induced pleurisy, articular inflammation zymosan-induced, Freund's complete adjuvant-induced inflammation zymosan-induced peritonitis, and carrageenan-induced adhesion and rolling experiment models. All doses of G. celosioides (300, 700, and 1000 mg/kg) significantly reduced edema formation in all the intervals evaluated, whereas the mechanical hyperalgesia was reduced 3 hours after the carrageenan injection. The cold hyperalgesia was significantly decreased 3 (700 mg/kg) and 4 hours (700 and 1000 mg/kg) after the carrageenan injection. Ethanolic extract of G. celosioides at 1000 mg/kg reduced the total leukocyte number, without interfering in the protein extravasation in carrageenan-induced pleurisy model. Ethanolic extract of G. celosioides (300 mg/kg) was also able to reduce significantly the leukocyte migration in zymosan-induced articular edema, while a reduction of the adhesion and migration and leukocyte rolling was induced by the ethanolic extract of G. celosioides (300 mg/kg) in zymosan-induced peritonitis. In Freund's complete adjuvant-induced inflammation model, an edema formation and mechanical hyperalgesia reduction were induced by the ethanolic extract of G. celosioides on day 22, whereas the cold allodynia was reduced on day 6 of treatment with the extract. These results show that ethanolic extract of G. celosioides has antihyperalgesic and antiarthritic potential in different acute and persistent models, explaining, at least in part, the ethnopharmacological relevance of this plant as a natural analgesic agent.